Climate change and safe design of ship structures. (1st February 2018) - Bitner-Gregersen, Elzbieta M.; Vanem, Erik; Gramstad, Odin; Hørte, Torfinn; Aarnes, Ole Johan; Reistad, Magnar; Breivik, Øyvind; Magnusson, Anne Karin; Natvig, Bent
Abstract: The paper addresses projected changes of wave climate in the North Atlantic and their impact on the safe design of ships, with a particular focus given on associated uncertainties. The Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) uses four scenarios for future greenhouse gas concentrations in the atmosphere called Representative Concentration Pathways (RCP). Two of these scenarios are applied to investigate how sensitive the future North Atlantic wave climate is to the emissions they represent. Winds obtained from six global climate models have been used to simulate waves for a historical period at the end of last century and to project waves for a future period towards the end of this century for these two scenarios. Based on these projections, possible changes in extreme wind and waves are investigated and the associated uncertainties are discussed. The occurrence of rogue-prone sea states which may trigger generation of rogue waves in the past and future climate is also studied. It is shown how the scientific findings on uncertainties related to climate change projections and rogue waves can be incorporated in the risk-based approach used in current design practice of tankers, and ship structures in general. The potential effect of climate change on the safety level of current design practice for tankers is demonstrated. Finally, the paper discusses how structural design of ships can be upgraded to account for climate change and rogue waves without necessarily leading to significant economic consequences. Highlights: Climate change. Waves. North Atlantic. Uncertainties of wave climate projections. Impact on ship design.